Observations on mineral transformations and potential environmental consequences during the oxidation of iron sulphide-rich materials in incubation experiments - Shi, X.; Oldmeadow, D.; Aspandiar, Mehrooz (Blackwell Publishing Ltd, 2015)
This paper attempts to acquire a good understanding of the formation and evolution of acid sulphate soils (ASS), as well as to assess the consequent environmental impacts. An incubation experiment to simulate the development of ASS under various weathering scenarios was set up. Fresh monosulphidic black ooze (MBO) material was divided into three parts and each was subjected to different drying and rewetting regimes by controlling an artificial water table in an incubation cell. The observations focused on the changes in mineralogy of the material and reflectance spectral changes during the oxidation process, and the ionic composition and chemical status of the solutions generated. Mineralogical investigations with hyperspectral and XRD analysis showed that frequent inundation produced extensive surface oxidation and a change from iron sulphide minerals to stable end members such as goethite. For the material experiencing moderate or occasional inundation, oxidation was less advanced and a different secondary mineral suite, with iron sulphate minerals such as jarosite, was present. Solutions generated from all the incubation cells were generally acidic with pH around 3.5, indicating that sulphide oxidation occurred rapidly in all cells. Sulphate concentrations in solutions from the different cells were calculated from the measurements of SO42− and other anions in solutions and may approximate the rates of sulphide oxidation. Potential environmental impacts were illustrated in terms of soil acidity, salinity and trace metal release, and the effects of the different wetting/drying regimes on the oxidative process also provided insight into potential weathering effects in a changing climate.